2015
DOI: 10.19108/koers.80.2.2227
|View full text |Cite
|
Sign up to set email alerts
|

The reawakening of teaching through aesthetics in education: Students’ perspectives

Abstract: A multidisciplinary approach to teacher education involves drawing from multiple pedagogies within disciplines, in particular the use of aesthetic methods of teaching, to redefine teaching through continuous reflection. This article reports on the process of pre-service students' interpretation of the sensory contemplation of aesthetic perceptiveness within their academic programmes at a higher education institution and explores how students internalised and applied these aesthetic qualities in their practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…In the first study, students who learned using Papora application showed that they were satisfied because the lesson could be easily understood and learned [42]. Another researcher mentioned that design aesthetics is one of the greater degrees of satisfaction that leads to a greater degree of loyalty [43].…”
Section: A Research Question 1 (Rq1)mentioning
confidence: 99%
“…In the first study, students who learned using Papora application showed that they were satisfied because the lesson could be easily understood and learned [42]. Another researcher mentioned that design aesthetics is one of the greater degrees of satisfaction that leads to a greater degree of loyalty [43].…”
Section: A Research Question 1 (Rq1)mentioning
confidence: 99%
“…Nitekim Okan'a (2002) göre, estetik eğitim tek başına bir eğitim biçimi değildir ve görsel sanatlar eğitimi derslerinde çok alanlı sanat eğitimi yöntemiyle birlikte verilmelidir. Ramndhani ve Ramsaroop (2015), estetik yoluyla verilen eğitimin öğrencilerin bakış açısına etkisini araştırdıkları çalışmalarında öğretmenlerin öğretim stratejilerini kullanırken zorlandıklarını ancak resim ve modeller gibi görsel araçları sınıftaki öğrencilerin yaş grubuna uyarladıklarında estetik üzerine grup tartışmasını geliştirebildikleri sonucuna ulaşmışlardır. Bu durum estetik eğitimde yaş seviyesinin görsel algı üzerindeki etkisi açısından araştırma sonuçları ile örtüşmektedir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Bu doğrultuda estetik değer eğitiminin sadece sanat dersleri için değil, diğer disiplin alanlarda da yaratıcılığın, hayal gücünün ve eleştirel düşünme becerisinin gelişimi için bir gereksinim olarak eğitim öğretim ortamına entegre edilmesinin gerekliliği anlaşılmaktadır. Nitekim estetik değer eğitiminin öğrenmede merak ve deneyimi arttırdığı, eğitimin büyüleyici ve heyecan verici bir deneyim olarak değerlendirilmesine yol açtığı vurgulanmaktadır (Drake, 1998ve Hansen, 2005'den aktaran Ramdhani ve Ramsaroop, 2015). Ancak yapılan çalışmalar okullarda estetik değer eğitimine gereken önemin verilmediğini, estetik değerin saygı, sevgi, hoşgörü gibi diğer değerlere oranla daha az önemli bulunduğunu ve günümüzde oldukça yaygın bir alanda kullanılmasına rağmen estetik kavramının neyi kastettiği ya da karşıladığının tam olarak bilinmediğini ortaya koymaktadır (Balcı ve Yanpar Yelken, 2013;Çelikkaya ve Filoğlu, 2014;Sevim, Hisarcıklılar ve Feyzioğlu, 2012).…”
Section: Introductionunclassified